BENTUK DAN TEKNIK GERAK BAGI IBU-IBU USIA LANJUT DALAM TARI TAMPURUANG DI KENAGARIAN SARIBU RUMAH GADANG SOLOK SELATAN - Nada Aulia Arva; Wimbrayardi (Universitas Negeri Padang, 2026)
This research is motivated by the declining public interest in Tampuruang dance performances. Currently, Tampuruang dance has begun to be neglected, especially by teenagers. The aim of this study is to revive interest and to understand the Forms and Movement Techniques of Tampuruang Dance as well as the meaning of movements in the local cultural context. The method used in this study is a qualitative approach with a descriptive method. The research instrument is the researcher themselves, supported by tools such as writing materials, a camera, and video or audio recordings. Data collection techniques include observation, interviews, and documentation. The results of the study indicate that Tampuruang Dance has core movements as well as movements that carry meaning, consisting of 7 movement forms and techniques that emphasise leg and arm movements.